A Critique on the Book “近世の三大改革 “The Great Triple Reform in Early Modern Japan - Ali Golmohammadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی, 2020)
What contradictions and crises made the Shogunate take countermeasures in the form of three major reforms (Kyōhō, Kinsei, and Tenpō) in early modern period Japan (Kinsei)? The author’s critical study of the topic focused on the appellation “three major reforms,” their renown and confinement to three periods by the Shogunate, and the explanation is within the two historical perspectives of “Good and Bad Governance Alternation” and “Tension and Relaxation.” Expressing his own definition of “reform,” and some examples in each period, the author tries to criticize fairly the bad governance and its instances. The book provides its Iranian readers with new and informative content. The book review is aimed at explaining the reforms and highlighting the significance of the reforms’ socio-political potential in Japanese modernization and also stressing the importance of the historical period, which was unintentionally neglected by the writer and suggesting Thomas Spragens’s theory of crisis as an alternative for a better analysis. A thorough study of the Shogunate’s akin and appointee reformers needs a political theory rather than a historical one. Focusing on governmental reform to prevent the dissolution of the system hindered the author’s attention to the nature of the reform and the important consequences.